Situation that presents the spelling in Cuba and in other Spanish-speaking countries at the end of the first decade of XXI century. - Miriam Gutiérrez Escobar; Raúl López Fernández; Rocío Dalia Rodríguez Gutiérrez; Rosa María Rodríguez Arencibia; Loreta Sánchez Ortiz; Rachel Yanes Seijo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
The Spanish language is the social communication link from a large number of people distributed in different regions of the world and deserve protection and preservation. The correct spelling of the texts is a way to defend and preserve our language, because the written word is the one permanently fixed language. Speaking of the correct spelling of words we are talking about spelling, this item is diffucult today. The aim of this paper is to analyze how the situation presents spelling of Spanish-speaking countries in the late first decade of the twenty-first century, through a literature review to update readers and constitutes a starting point for further work. A literature search was conducted in different countries, among which are: Spain, Mexico, San Salvador, Nicaragua, Chile, Peru, Colombia, Argentina and Cuba, where it was observed that the spelling is deficient in all matters, covers all levels of education, even professionals, as well as widespread concern about their treatment.